From challenge to competence: the role of learning engagement in mediating stress and performance among clinical medical students in English-medium dental education - Liu, Runheng; Lin, Jiahui; Chen, Xiaoyan; Hou, Yuhan; Liu, Guanqi; Wang, Yan (Frontiers in Medicine, 2025)
BackgroundThe adoption of English-medium instruction (EMI) in medical education has sparked ongoing debate, particularly in non-native English-speaking contexts. While EMI is increasingly applied to clinical medical programs, its effectiveness within dental education remains underexplored, especially with regard to changes over the duration of a course. This study aimed to examine the dynamic impact of instructional language (EMI vs. CMI) on medical students’ perceived academic stress, self-regulated learning engagement (SRLE) and academic performance in a dental course.Materials and methodsA quasi-experimental design was employed with 123 undergraduate medical students enrolled in a stomatology course. Participants were allocated to an EMI group (n = 41) or a Chinese-medium instruction (CMI) group (n = 82). Perceived stress and SRLE were measured at two time points: 1 month after course initiation (T1) and upon course completion (T2). Academic performance was evaluated via final examination and structured review writing tasks. Statistical analyses included between- and within-group comparisons, correlation analysis, hierarchical regression, and mediation modeling.ResultsAt T1, EMI students reported significantly higher stress and SRLE levels compared to CMI peers. While stress decreased over time in both groups, EMI students maintained consistently high engagement. T2 engagement significantly predicted review writing performance, fully mediating the effect of instructional language. Notably, the EMI group achieved higher review scores, though no significant difference was found in final exam performance. Correlation patterns diverged over time, with stress positively associated with engagement only in the EMI group at T2.ConclusionDespite elevated stress levels, EMI students demonstrated superior learning engagement and higher-order academic performance. These findings suggest that EMI, when supported by adaptive engagement, may effectively foster interdisciplinary competence in dental education. Tailored pedagogical strategies are warranted to optimize stress adaptation and enhance learning outcomes in EMI environments.